2019
DOI: 10.1016/s2095-3119(18)62053-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of varieties and development of production technology in Egypt wheat: A review

Abstract: Wheat was the first crop grown in Egypt, and it remains highly important. Egypt is the largest wheat importer in the world and consumes an extensive amount of bread. It is imperative for wheat scientists to decrease the large gap between production and consumption. Wheat yields in Egypt increased 5.8-fold (6.7 billion kg) between 1961 and 2017 due to variety improvement and the use of better planting methods such as the raised bed method, ideal sowing date, surge flow irrigation and farm irrigation systems, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The Egyptian hybrid programs have continued to release new cultivars with improved agronomic characteristics such as salinity tolerance, short plant height, high yield, water deficit resistance, early maturity, and more tillers. Of all wheat pathogenic fungi, the released cultivars by the Egyptian breeders up to date have been evaluated only for their resistance to rusts due to their severe threat to the wheat crop in Egypt [33]. For each wheat-growing governorate, specific wheat cultivars have been recommended by the Egyptian Ministry of Agriculture and Land Reclamation depending on the cultivar's suitability to the climatic conditions in a given governorate in order to achieve the highest wheat productivity per unit area.…”
Section: Discussionmentioning
confidence: 99%
“…The Egyptian hybrid programs have continued to release new cultivars with improved agronomic characteristics such as salinity tolerance, short plant height, high yield, water deficit resistance, early maturity, and more tillers. Of all wheat pathogenic fungi, the released cultivars by the Egyptian breeders up to date have been evaluated only for their resistance to rusts due to their severe threat to the wheat crop in Egypt [33]. For each wheat-growing governorate, specific wheat cultivars have been recommended by the Egyptian Ministry of Agriculture and Land Reclamation depending on the cultivar's suitability to the climatic conditions in a given governorate in order to achieve the highest wheat productivity per unit area.…”
Section: Discussionmentioning
confidence: 99%
“…In both seasons, seeding wheat by drilling method (SM 1 ) gave the greatest increase for all studied growth traits. It might be attributed to drilling is an advisable planting method due to uniform seed distribution in the field and seeding at desired depth which ensures higher emergence and good subsequent crop growth as well as increases the utilization efficiency of light, water, fertilizer and higher root growth, which lead to enhance plant growth (Tao et al, 2017;Abdelmageed et al, 2019). Tamirat & Mekides (2020) indicated that the drilling planting method has able a good leaf length, the highest mean values of leaf number and is a better way to maximize the productivity of wheat.…”
Section: Effect Of Sowing Methodsmentioning
confidence: 99%
“…So, the farmer selects the proper method depending on soil type and the preceding crop which leads to facilitating plants to utilize the land, and optimum plant population in the field, and good subsequent crop growth (Singh & Sharma, 2019;Angelique et al, 2020). In Egypt, most farmers prefer the broadcasting method because it saves time, whereas progressive farmers and research scientists use the drilling sowing method due to uniform seed distribution in the field and sowing at desired depth which results in higher germination, to save the labor in controlling weeds and increases the utilization efficiency of light, water, fertilizer and other resources (Tao et al, 2017), but only 27% of the farmers currently practice drill sowing (Abdelmageed et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, the total area cultivated with wheat is 1.4 million ha, with a yield of 9 million tons (FAO, 2021). However, there is still a big gap, (~50%) between production and consumption (Abdelmageed et al, 2019). Egyptian land available for new agricultural expansion projects is generally categorized as semiarid land.…”
Section: Introductionmentioning
confidence: 99%